Pengaruh Pemberian Pupuk Organik Cair dari Limbah Kulit Buah Pisang Lilin (Musa paradisiaca L.) terhadap Pertumbuhan Tanaman Bayam Merah (Amaranthus tricolor L. var Blitum rubrum) - Diatri, Eka Aulia; Marlina, Leni; Zuhri, Rozana (BIOCOLONY, 2018)
The lack of utilization of waxy banana peel waste in Merangin District is a sourceof environmental pollution. Wax banana peel waste has the potential as a liquidorganic fertilizer. This study aims to determine the effect of giving liquid organicfertilizer from wax banana peel waste on the growth of red spinach plants and todetermine the dose of liquid organic fertilizer from waxy banana peel waste whichgives the best results for the growth of red spinach plants. The study used aCompletely Randomized Design (CRD) of one factor, consisting of 6 treatmentsnamely P0 (0 ml / control), P1 (10 ml), P2 (20 ml), P3 (30 ml), P4 (40 ml) and P5(50 ml) with 4 repetitions. The parameters of this study were plant height, numberof leaves, leaf surface area and root length. Data were analyzed using varianceanalysis and continued with Duncan test 5%. The results showed that liquid organicfertilizer of wax banana peel waste had a significant effect on the number of leaves,but did not give effect to plant height, leaf surface area and root length of redspinach. Liquid organic fertilizer of wax banana peel waste 20 ml dose gives thebest results on the number of red spinach plant leaves.